Evaluation of the User Experience on Mobile Fitness Applications - Almeida, Rodrigo Lucas; Carneiro, Nayana; Silva, Deivith; Darin, Ticianne G. R. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
This paper presents an evaluation of the quality of experience of use and the resources provided by the Mobile Fitness Applications (MFAs) Nike+Running and RunKeeper (MFAs). In this study, we used analytic and empirical evaluation methods, exploring usability, and user experience to verify if they supply the users’ needs. Initial results show the relation between motivational and emotional aspects and MFAs resources, as well as the quality of its resources. We present the first part of a research whose final objective is to identify what characteristics are necessary for designing MFAs capable of motivating users to engage and evolve on physical activity.